2021
DOI: 10.3390/ijms221910572
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Cancer Stem Cells in Tumor Progression: New Therapeutic Perspectives

Abstract: Tumor burden is a complex microenvironment where different cell populations coexist and have intense cross-talk. Among them, a heterogeneous population of tumor cells with staminal features are grouped under the definition of cancer stem cells (CSCs). CSCs are also considered responsible for tumor progression, drug resistance, and disease relapse. Furthermore, CSCs secrete a wide variety of extracellular vesicles (EVs) with different cargos, including proteins, lipids, ssDNA, dsDNA, mRNA, siRNA, or miRNA. EVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 187 publications
(222 reference statements)
0
21
0
Order By: Relevance
“…L-EVs have a size range of about 100–1000 nm and are of plasma membrane origin [ 133 ]. S-EVs are of endocytic origin and their size is within a range of 50-130 nm [ 133 ].…”
Section: Mirna Studies Of Depression and Antidepressant Treatments Investigating Blood And Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…L-EVs have a size range of about 100–1000 nm and are of plasma membrane origin [ 133 ]. S-EVs are of endocytic origin and their size is within a range of 50-130 nm [ 133 ].…”
Section: Mirna Studies Of Depression and Antidepressant Treatments Investigating Blood And Bodymentioning
confidence: 99%
“…L-EVs have a size range of about 100–1000 nm and are of plasma membrane origin [ 133 ]. S-EVs are of endocytic origin and their size is within a range of 50-130 nm [ 133 ]. EPs on the other hand are small protein-nucleic-acid complexes of unknown cellular compartment and are less than 50 nm in size [ 134 ].…”
Section: Mirna Studies Of Depression and Antidepressant Treatments Investigating Blood And Bodymentioning
confidence: 99%
“…The heterogeneous compositional structures of the biological tissues lead to distinctive chemical and physical processes compared to the homogeneous man-made materials, which restricts the sensitivity, accuracy, and efficiency of signal transductions through biosensor interfaces [ 45 , 46 ]. The mismatch in mechanical properties, including toughness, flexibility, and adhesion ability, will lead to immune rejection and disable the long-term usage of sensing devices [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that EVs derived from CSCs can induce tumor growth, metastasis, participating in angiogenesis and maintaining the stem cell phenotypes ( 185 188 ). EVs released from CSCs containing multiple cargoes, including proteins and multiple RNA ( 189 ). EVs can make the microenvironment to change in the direction of promoting tumor occurrence and metastasis.…”
Section: Regulation Of Hcc By Different Cell-derived Evs In the Micro...mentioning
confidence: 99%